Holographic detection of nanoparticles using acoustically actuated nanolenses - Aniruddha Ray (Nature Portfolio, 2020)
Detection of small, translucent particles is challenging due to their low inherent scattering. Here, the authors present an easy, high-throughput, label-free method for detecting nanoparticles in low volumes of liquids on a disposable chip, using an acoustically actuated lens-free holographic system.